Areas of Polygons With Coordinates of Vertices From Horadam and Lucas Numbers - Čerin, Zvonko (Sarajevo Journal of Mathematics, 2018)
We consider several classes of polygons in the plane with coordinates of points from the Horadam and (general) Lucas numbers. Our goal is to determine formulas for oriented areas of these polygons. Some of our formulas are for polygons with any number of vertices while others deal only with triangles, quadruples and pentagons.